1999
DOI: 10.1080/088800199276877
|View full text |Cite
|
Sign up to set email alerts
|

Postinfection Purpura Fulminans in a Patient Heterozygous for Prothrombin G20210a and Acquired Protein S Resistance

Abstract: Purpura fulminans usually consists of large, often symmetrical, spreading ecchymosis, which may later develop into extensive areas of skin necrosis and peripheral gangrene. Postinfectious purpura fulminans associated with an autoantibody directed against protein S has been described. The interaction and the contribution of recently described mutations such as factor V Leiden and prothrombin G20210A to the development and progression of postinfectious purpura fulminans and venous thrombosis is not known. The au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 6 publications
0
12
1
Order By: Relevance
“…12 The clinical manifestations can also go along with streptococcal coinfection, 12,15 with the simultaneous presence of procoagulant antiphospholipid antibodies 13,16 and/or a concomitant thrombophilic disorder. 17 A severe PS deficiency, failing to support activated PC, allows an uncontrolled and excessive production of thrombin, leading to widespread and systemic intravascular fibrin deposition, that is, DIC. This has been demonstrated in patients with postinfectious PF who were showing increased plasma levels of prothrombin fragments 1+2 12,13 and in vitro by showing an acquired resistance to activated PC in the presence of anti-PS antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…12 The clinical manifestations can also go along with streptococcal coinfection, 12,15 with the simultaneous presence of procoagulant antiphospholipid antibodies 13,16 and/or a concomitant thrombophilic disorder. 17 A severe PS deficiency, failing to support activated PC, allows an uncontrolled and excessive production of thrombin, leading to widespread and systemic intravascular fibrin deposition, that is, DIC. This has been demonstrated in patients with postinfectious PF who were showing increased plasma levels of prothrombin fragments 1+2 12,13 and in vitro by showing an acquired resistance to activated PC in the presence of anti-PS antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Anecdotal reports have indicated that the presence of congenital thrombophilia may exacerbate the coagulopathy associated with severe infection and may even result in purpura fulminans. [55][56][57][58][59] Indeed, various coagulation defects seem to be associated with an aggravated coagulation response to infectious agents or sepsis, although a systematic overview is missing. 60,61 Experimental studies seem to confirm the hypothesis.…”
Section: Prothrombotic Mechanisms In Sepsismentioning
confidence: 99%
“…Finally, characterization of epitopes on PS was reported by one team [7]. Anti‐PS antibodies have also been found in children with purpura fulminans after infections other than varicella [8,9].…”
Section: Introductionmentioning
confidence: 99%